Multi-Drug Resistance of Mycobacterium Tuberculosis – the Problem of Modern Phthisiology - E. Yu. Zorkaltseva; O. A. Vorobyeva; E. D. Savilov; O. B. Ogarkov (Acta Biomedica Scientifica, 2019)
The 21st century is characterized by the exacerbation of the problem formation and spreading of drug-resistant strains throughout the world. Genetic mutations of Mycobacterium tuberculosis lead to the formation of drug-resistant forms because of long-term use of anti-tuberculosis drugs. The Russian Federation is among the top three countries with a high burden of tuberculosis with multidrug resistance (MDR). The estimated number of cases of tuberculosis with MDR in the Russian Federation was 60,000, which corresponds to half the burden of the European Region in 2015. In the Irkutsk region from 2014 till 2018 the proportion of TB cases with MDR cases increased from 15.2 % to 18.3 %. According to the reference laboratory of the Irkutsk Regional Clinical Tuberculosis Hospital, a significantly higher level of MDR among primary diagnosed was registered in the cities (27.7 %) and the lowest in rural areas of the region (16.5 %). Among the cohorts of patients with tuberculosis, the highest proportion of MDR was in the northern territories of the region (43.1 %), in Irkutsk district (41.2 %) and in large cities, including Irkutsk (38.5 %). Positive correlations were established between cohort of primary diagnosed TB with MDR and among populations in areas with high morbidity along the railway (r = 0.91; p = 0.00001), in the Irkutsk region (r = 0.89; p = 0,00008), and also in the Irkutsk city (r = 0.91; p = 0.00002). This is probably due to the influence of reservoir of tuberculosis infection formed in these localities. The regulatory documents of the Ministry of Health of the Irkutsk Region was developed on the basis of the data obtained, and they include recommendations for improving the diagnosis of tuberculosis in the region using fast and accelerated microbiological diagnostic methods.